The Role of Digital Marketing in Shaping Customer Retention: A Mediated Analysis of Perceived Value - Romagia, R.; Indrayani, I.; Damsar, D. (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study aims to analyze the effect of digital marketing on customer retention by considering customer perceived value as a mediator. The method used is a quantitative approach with a descriptive-explanatory design, a sample of 250 respondents was collected from customers who interact with the company through digital platforms and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results show that digital marketing has a significant positive influence on customer retention, with customer perceived value serving as a mediator that strengthens this relationship. The findings indicate that effective digital marketing strategies, such as content personalization and responsive interactions, can increase customer perceived value, with implications for increasing customer loyalty. This research offers original value by emphasizing the importance of local context in the implementation of digital marketing strategies, especially in non-urban areas such as Indragiri Hulu. The implications of these findings suggest that companies should focus on increasing the value perceived by customers through a more personalized and relevant shopping experience. Thus, this study not only provides new insights into the relationship between digital marketing and customer retention, but also provides practical recommendations for companies to design more effective marketing strategies, which can ultimately increase customer loyalty and business sustainability.